(untitled) (Journal of The Colloquium for Information Systems Security Education, 2019)
Cybersecurity is a broad, dynamic, and ever-changing field that is difficult to integrate into undergraduate Computer Science (CS) curriculum. The absence of sanitized labs coupled with the requirement of specialized faculty to teach the subject pose obstacles many primarily undergraduate colleges face in adopting cybersecurity education. In this paper we describe a set of labs that have been implemented using the Global Environment for Network Innovations (GENI) cloud infrastructure as a solution to teaching experientially with low overhead. These labs are developed for different levels of experience, based on Capture The Flag (CTF) competitions that include short questions and answers, scenario based exercises, and upper level research skills. Curriculum for Liberal Arts Institutions is presented starting from the core general education as a vehicle to bring cyber security to a diverse population of non-CS majors and moving to introductory and upper level CS courses. These labs and curriculum are part of the project CyberPaths (Cyber security Paths) with goal to broaden the path to cybersecurity profession for a diverse population of Liberal Arts students.